Air Pollution Trend Analysis in Hangzhou during the Asian Games (International Journal of Scientific Research in Science and Technology, 2026)
This study examines the temporal dynamics of air pollution in Hangzhou, China, during 2023, with a particular focus on the Asian Games period (September-October 2023). Monthly average concentrations of six criteria pollutants (PM2.5, PM10, NO2, O3, SO2, and CO), together with four meteorological parameters, were used to evaluate the effectiveness of short-term regulatory interventions implemented for the mega-event. The results indicate substantial reductions in primary pollutants during the Games, especially NO2 (19 μg/m³ in September compared with an annual average of 30.1 μg/m³) and PM10 (40.5 μg/m³ during the Games versus 53.4 μg/m³ prior to the event), reflecting the effectiveness of traffic and industrial control measures. In contrast, ozone concentrations remained elevated (125.2 μg/m³), likely driven by favourable photochemical conditions, highlighting the challenges associated with managing secondary pollutants. A pronounced rebound effect was observed in November-December, with PM2.5 and NO2 increasing by 69.2 % and 76.5 %, respectively, relative to Games-period levels. Overall, the findings demonstrate that while temporary emission controls can deliver short-term air quality improvements, sustainable urban air quality management requires integrated, long-term strategies, and the study provides policy-relevant insights for future mega-events in rapidly developing urban environments.